Moroccan genome project: genomic insight into a North African population - Elmostafa El Fahime; Souad Kartti; Mohammed Walid Chemao-Elfihri; Rihab Festali; Mohammed Hakmi; Azeddine Ibrahimi; Saber Boutayeb; Lahcen Belyamani (Communications Biology)
Abstract Africa’s 1.5 billion people are underrepresented in genomic databases. The African Genome Variation Project exclusively focuses on Sub-Saharan populations, making Morocco, located in North Africa, a valuable site for studying genetic diversity. Understanding genetic variation and customized therapy requires population-specific reference genomes. This study presents Phase 1 results from the Moroccan Genome Project (MGP), which sequenced 109 Moroccan genomes. We report over 27 million variants, including 1.4 million novel ones, of which 15,378 are highly prevalent in the Moroccan population. Furthermore, we propose a Moroccan Major Allele Reference Genome (MMARG), generated using high-coverage consensus sequences from the 109 whole genomes. This MMARG represents more accurately the Moroccan genetic variation than GRCh38. This baseline study also generates an informative genetic variation database that supports regional population-specific initiatives and precision medicine in Morocco and North Africa. The results stress the necessity of population-relevant data in Human genetic research.